Poly(urethane methacrylate-co-glycidyl methacrylate)-supported-polypropylene biphasic membrane for lipase immobilization - Pujari, N. S.; Vaidya, Bx; Bagalkote, S.; Ponrathnam, S.; Nene, Sanjay (Journal of Membrane Science, 2006)
Polypropylene (PP) was hydrophilized by coating followed by UV curing of a blend of 2-hydroxyethyl methacrylate (HEMA) terminated polyurethane prepolymer and glycidyl methacrylate (GMA). This allows formation of a hydrophobic membrane with increased surface hydrophilicity, biocompatibility and stability. Candida rugosa lipase (CRL) was covalently immobilized on this membrane using 5% glutaraldehyde as a crosslinking agent for post immobilization stabilization of enzyme on membrane. The membrane obtained was placed in a batch membrane reactor where a model esterification of oleic acid with octanol was studied. Under optimum conditions, the biocatalytic membrane gave a specific activity of 796.27 units/mg and 90.26% activity yield. Moreover, there was 85. 10% retention of specific activity. The biocatalytic membrane was observed to retain about 84.23% of its synthetic activity after six cycles. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Candida rugosa lipase; Enzyme immobilization; membrane bioreactor; urethane methacrylate

Production of polyunsaturated fatty acids in recombinant lipomyces starkeyi through submerged fermentation - Salunke, Devyani; Manglekar, Rupali; Gadre, Ramchandra V.; Nene, Sanjay; Harsulkar, Abhay M. (Bioprocess and Biosystems Engineering, 2015)
Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60 % of its biomass and where genetic transformation can be achieved. In our earlier work, Delta 15 desaturase gene (AEP37840) from flax was transformed into L. starkeyi. In the present work, we report optimization of medium for the production of omega-3 enriched oil from this transformed yeast. A basic medium containing 20 g/l glucose as a carbon source and 10 g/l yeast extract as a nitrogen source was used during fermentation. At regular time intervals, glucose was fed to maintain high C:N ratio (65:10) during fermentation. Under the most favorable conditions, dry biomass and total lipid content were 18 and 7.29 g/l, respectively. Prior to genetic transformation, L. starkeyi contained 56.03 mg/l DHA along with 71.4 mg/l EPA and 42.2 mg/l ALA. Genetic engineering of this yeast resulted in a strain that produced 1080 mg/l DHA (17.4 %) along with 74.28 mg/l EPA and 126.72 mg/l ALA possibly through modification of PUFA biosynthetic pathway. To the best of our knowledge, this is a first report of DHA enrichment and opens up avenues for LCPUFA production through L. starkeyi.
Keywords: Fermentation; LCPUFA; Lipid production; Oleaginous yeast